Minimal Invasive Management of Anastomosis Leakage after Colon Resection - Esin Kabul Gürbulak; İsmail Ethem Akgün; Ayhan Öz; Sinan Ömeroğlu; Muharrem Battal; Fevzi Celayir; Mehmet Mihmanlı (Case Reports in Medicine)
The gold standard of surgical treatment of colorectal anastomotic leak is abdominal drainage of collected fluid and stoma formation. Conventional laparotomy has been the preferred approach for treatment. However, both laparoscopic surgical techniquesand endoscopic stenting have gained popularity over the past years as minimal invasive approaches, especially in the management and treatment of perforations of the gastrointestinal system. We present here a successful treatment with a minimal invasive management of anastomosis leak in the early postoperative period after colon resection in a 62-year-old female patient who had undergone urgent laparoscopic intra-abdominal lavage and drainage followed by endoscopic stenting.